Local government finances - A case study of Andhra Pradesh - Narayan, Jayaprakash; Sanjay, P. (2004)
The working of local governments and their ability to improve the quality of grassroots democracy is contingent on the availability of adequate financial resources at their disposal. Transfers from state and central governments are shown as revenue resources of local governments, but they have little discretion as the fund are given for a specified scheme or in the form of tied grants or matching grants. This financial dependence implies that local bodies are not `self-governments' but are functioning as agents of state and Union governments. A sincere effort is needed to make the local bodies truly `self-governing' representative of local people by feeding them with requisite independence and funds for local development. - Reproduced.
Keywords: Local government - India - Andhra Pradesh; Local government